Orocecal Transit Time in Normal Adults at Cipto Mangunkusumo National General Hospital, Jakarta - Paulus Simadibrata; Rudolf Simadibrata; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2002)
Helicobacter pylori has been known as a cause of chronic gastritis, a predisposition to gastric and duocenal ulcers, and a class I gastric carcinogen. Throughout the world, H. pylori infection is very common, reaching 40% -50% of the population in developed nations and 80% – 90% of the population in developing nations. Several techniques have been used to detect H. pylori infection, such as the urea breath test, rapid urease test, serological test, as well as biopsies of gastric or duodenal tissues for culture and histopathology. In this review article, we will discuss a relatively new method to detect H. pylori antigen in stools with enzyme immunoassay, and comparisons with other standard techniques. However, the H. pylori stool antigen test is not yet commercially available in Indonesia.Key words: Helicobacter pylori - stool antigen - enzyme immunoassay